2015
DOI: 10.1002/ijop.12212
|View full text |Cite
|
Sign up to set email alerts
|

I will help you because we are similar: Quality of contact mediates the effect of perceived similarity on facilitative behaviour towards immigrants

Abstract: This research aimed to analyse interpersonal behaviour towards immigrants by exploring related psychosocial variables such as intergroup similarity and quality of intergroup contact. A new interpersonal behavioural tendencies scale was developed. In Study 1, Spanish participants reported their willingness to take different actions towards a Moroccan (i.e. a devalued target, n = 132) or an Ecuadorian (i.e. a valued target, n = 138), perceived intergroup similarity and quality of intergroup contact. Multigroup c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 20 publications
0
15
0
1
Order By: Relevance
“…Perceived similarity refers to the extent that a user is perceived as similar or dissimilar to other users which is an important predictor of attitudes [20]. Based on the extant studies [21], the present research conceptualized perceived similarity as internal similarity and external similarity.…”
Section: Perceived Similaritymentioning
confidence: 99%
See 2 more Smart Citations
“…Perceived similarity refers to the extent that a user is perceived as similar or dissimilar to other users which is an important predictor of attitudes [20]. Based on the extant studies [21], the present research conceptualized perceived similarity as internal similarity and external similarity.…”
Section: Perceived Similaritymentioning
confidence: 99%
“…On the other hand, extant studies also proposed that there are positive relationships between internal similarity and interpersonal interaction attitudes [20]. Past researches pointed out that individuals with similar attitudes are more likely to communicate with each other [21].…”
Section: Perceived Similaritymentioning
confidence: 99%
See 1 more Smart Citation
“…In line with this work, we expect that perceived similarity between groups will predict preferences for culture adoption as well. Members of host societies are often inclined to perceive immigrants' cultural differences as potentially threatening, and discordance between the perspectives and acculturation preferences of immigrants and host society members can introduce intergroup tensions (López-Rodríguez, Cuadrado, & Navas, 2017;Piontkowski, Rohmann, & Florack, 2002;Zagefka, Nigbur, González, & Tip, 2013). By contrast, greater perceived similarity with immigrants tends to be associated with lower perceptions of threat and more positive views about relations with immigrants among host society members (López-Rodríguez et al, 2017).…”
Section: Acculturation Preferences and Cross-group Relationsmentioning
confidence: 99%
“…The current issue of the IJP has a strong focus on psychological science related to these issues with five articles focused on attitudes and behaviour towards outgroups, social discrimination, and adjustment following war. For example, López‐Rodríguez, Cuadrado, and Navas () demonstrate the importance of perceptions of similarity for positive behaviour towards immigrants. Their three studies, conducted with almost 400 Spanish adults, revealed that quality of contact mediated the association between perceived similarity and facilitative behaviour towards immigrants.…”
mentioning
confidence: 99%